2001
DOI: 10.1128/aac.45.6.1930-1933.2001
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Inhibits Quorum Sensing in Pseudomonas aeruginosa

Abstract: We report that 2 g of azithromycin/ml inhibits the quorum-sensing circuitry of Pseudomonas aeruginosa strain PAO1. Addition of synthetic autoinducers partially restored the expression of the trancriptional activator-encoding genes lasR and rhlR but not that of the autoinducer synthase-encoding gene lasI. We propose that azithromycin interferes with the synthesis of autoinducers, by an unknown mechanism, leading to a reduction of virulence factor production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
267
4
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(293 citation statements)
references
References 30 publications
15
267
4
7
Order By: Relevance
“…These reductions coincided with reduced Las-and Rhl-dependent gene transcription and have been corroborated by microarray and proteomic studies (319,320), which found, in addition to QS gene misregulation, a reduction in levels of oxidative stress and motility-related genes but an increase in type III secretion (TTS)-related genes. The diminished response to oxidative stress conditions may account for the reduced cell viability in late stationary phase that was reported to occur with increasing concentrations of macrolides (318,319). Likewise, the finding that TTS was induced with exposure to AZM may explain the paradoxical finding that pretreatment of bacterial cultures with macrolides prior to intranasal inoculation in mice led to an enhanced lethal effect (321).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 49%
“…These reductions coincided with reduced Las-and Rhl-dependent gene transcription and have been corroborated by microarray and proteomic studies (319,320), which found, in addition to QS gene misregulation, a reduction in levels of oxidative stress and motility-related genes but an increase in type III secretion (TTS)-related genes. The diminished response to oxidative stress conditions may account for the reduced cell viability in late stationary phase that was reported to occur with increasing concentrations of macrolides (318,319). Likewise, the finding that TTS was induced with exposure to AZM may explain the paradoxical finding that pretreatment of bacterial cultures with macrolides prior to intranasal inoculation in mice led to an enhanced lethal effect (321).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 49%
“…Macrolide antibiotics have been shown to act as QS inhibitors at subinhibitory concentrations. For example, erythromycin has been reported to suppress production of P. aeruginosa hemagglutinins, protease, hemolysin and AHL signals [14], and studies have shown that azithromycin at sub-MIC concentrations affects QS-regulated virulence genes and biofilm formation in vitro [15][16][17] and in in vivo models of disease [18]. In the present study, we demonstrate that sub-inhibitory concentrations of azithromycin could dose-dependently reduce the haemolytic activity and biofilm formation in S. aureus.…”
mentioning
confidence: 55%
“…In a recent study, a screening of quorum-sensing-inhibiting molecules derived from the plant species Combretum albiflorum revealed that catechin has a negative impact on the production of quorumsensing-dependent virulence factors (Vandeputte et al, 2010). Subinhibitory concentrations of macrolides have been shown to be effective in inhibiting quorum-sensingdependent virulence both in vivo and in vitro (Imamura et al, 2004;Molinari et al, 1993;Sofer et al, 1999;Tateda et al, 2001). Furthermore, CF patients showed significant improvement in pulmonary function with the use of macrolides without any effect on the total Pseudomonas population (Fujii et al, 1995;Saiman et al, 2003).…”
Section: C M Antunes and Othersmentioning
confidence: 99%